Tenderised, Dehydrated Steaks of Freshwater Fish, Rohu: Preparation and Storage Characteristics - S.B., Warrier; K., Smruti; S., Rai; V., Yardi; V., Venugopal (Fishery Technology, 2025)
A process to prepare tenderised, dried steaks of freshwater fish, rohu (Labeo rohita) is reported. Steaks of fresh rohu were treated with papain for tenderisation, followed by dip treatment in sodium chloride solution. The brined steaks were dried either in a solar or tunnel dryer at a maximum temperature of 60oC Although solar drying required a longer drying time than tunnel drying, the products dried by both ways, had comparable proximate composition, with moisture content in the range of 15 to 16%, 59% protein and 5.7% crude fat. The aerobically packaged product, which had a water activity as low as 0.66, did not favour microbial growth when stored at ambient temperature. Tenderisation reduced hardness of dried product as observed by lower breaking force as well as sensory evaluation. The treatment also enhanced rehydration capacity of the dried steaks. Tenderisation followed by solar drying is suggested as a cost-effective process for value addition of rohu.